If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15ab + -9ab = 0 Combine like terms: 15ab + -9ab = 6ab 6ab = 0 Solving 6ab = 0 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Divide each side by '6'. ab = 0 Simplifying ab = 0 The solution to this equation could not be determined.
| 3[6-(y+1)]= | | 10x+5=6(5x-3) | | X=-3/4 | | 9ab-15ab= | | (4+x)x=91 | | 348/52 | | K/5-k=4 | | 9/16x=-4/48 | | 9/16x=-4/47 | | 3x=1/4 | | 96=2x+6y | | -5/9z=-1/4 | | 24x^3-16x^2-174x+90=0 | | 0.86=log(x) | | 1/12(12y)= | | 4y+9-y=8+2y-9 | | 0.50x+0.20(9.0-x)=4.20 | | 5x*1/5 | | (2/3)*w-5-5*w-4 | | r-2.2=-7.4 | | 4x^2-2x-55=0 | | 29/14(s)=2/7 | | 9x+5=43+2 | | 4x^2-2xy+5y^2=8 | | x(4X)=2(74) | | x-2y+2y=-1+2y | | 4(x+7)=73 | | (190-x)*5.4=x*8.8 | | (183-x)*7.5=x*6 | | 8ln(5x+10)=49.2 | | 9x^4+25=30x^2 | | 5/6x=18/35 |